The significance of changes in Mytella falcata (Orbigny, 1842) gill filaments chronically exposed to polluted environments - de Oliveira David, Jose Augusto [UNESP]; Salaroli, Renato B.; Fontanetti, Carmem S. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
The impact of pollutants in an organism can be observed by changes in functional complexity at different levels. Bivalve gills are suitable for histopathological analysis because of their structure and function. This study aimed at examining the morphology of Mytella falcata gill filaments from three sites in the Santos estuary (São Paulo, Brazil) with different levels of environmental degradation to identify possible changes in gill structure and discuss the significance of these alterations. For this purpose, histological, histochemical and ultrastructural techniques were used. The filaments of animals from site A (less impacted site) were intact, while in sites B and C, pathological changes were observed, such as: detachment of the epithelium in the intermediate zone, morphological changes of this epithelium, inflammatory process, increase in the number of mucous cells and cell turnover processes. These results suggest that the related changes are an attempt to prevent the entrance of pollutants through gill filaments into the entire organism and that cell turnover is the final way to compensate cell injury. (C) 2008 Elsevier Ltd. All rights reserved
Keywords: Bivalve; Cell turnover; Gill filaments; Histopathology; Pollutants; Santos estuary